Oxidative Stress Assays (arsenite and tBHP) in Caenorhabditis elegans - Collin Ewald; John Hourihan; T. Blackwell (Bio-Protocol, 2017)
Cells and organisms face constant exposure to reactive oxygen species (ROS), either from the environment or as a by-product from internal metabolic processes. To prevent cellular damage from ROS, cells have evolved detoxification mechanisms. The activation of these detoxification mechanisms and their downstream responses represent an overlapping defense response that can be tailored to different sources of ROS to adequately adapt and protect cells. In this protocol, we describe how to measure the sensitivity to oxidative stress from two different sources, arsenite and tBHP, using the nematode C. elegans.